Penggunaan Metode Bermain Modern melalui Media Kertas Bergambar dalam Mengembangkan Perilaku Ikhlas pada Anak Usia 5-6 Tahun di TK Buah Hati - Maknuun. S, Lu’luil; Damayanti, Eka; Salahuddin, Salahuddin; Rahmayanti, Rahmayanti (Faculty of Tarbiyah and Teacher Training, 2025)
Sincere behavior in children is a fundamental aspect of character development that will influence their attitudes and actions in the future. Therefore, early stimulation is crucial in instilling the value of sincerity. This descriptive quantitative study aims to foster sincere behavior through modern play methods based on illustrated paper media in children aged 5-6 years at Buah Hati Kindergarten, involving 17 children. The research instruments include illustrated paper media and observation sheets to assess the achievement of sincere behavior in children. Data analysis was carried out descriptively to broadcast the results of the treatment. The results showed that the average score of children's sincere behavior was 3.1, which means it is in the good category. This means using modern games based on illustrated paper media can encourage children to show a sincere attitude in the good category in interacting and doing activities. These findings indicate that a visual media-based play approach can be a recommended strategy in instilling sincere values, thus contributing to the formation of positive character in early childhood.